Clinical characteristics and surgical outcomes of lower lip mucocele: A retrospective study - Tae Young Jung (Journal of Korean Dental Association, 2026)
Purpose: This retrospective study investigated the clinical characteristics and surgical outcomes of lower lip mucocele at a single institution, focusing on the effectiveness of concomitant minor salivary gland removal in preventing recurrence.Materials and Methods: Medical records of 19 patients who underwent surgery for lower lip mucocele at Inje University Busan Paik Hospital between 2011 and 2025 were retrospectively reviewed. Patients were classified into two groups: 1) Group A (n = 16) achieved complete resolution with a single procedure including concomitant excision of the mucocele and the underlying minor salivary gland(s) and 2) Group B (n = 3) experienced recurrence after primary excision at our institution and subsequently underwent re-operation with additional minor salivary gland removal. Among the 19 patients, 4 (Cases 1, 6, 8, and 9) had previously been treated at outside facilities before referral.Results: The cohort comprised 12 males and 7 females, with a mean age of 22.1 years (range: 8–59 years). All 16 patients in Group A achieved resolution with a single operation. In Group B, recurrence developed within 2–5 weeks after primary excision; however, re-operation with additional minor salivary gland removal achieved resolution in all 3 patients. One patient developed transient commissure hypoesthesia, which partially recovered at final follow-up.Conclusion: Concomitant excision of the mucocele and the underlying minor salivary gland(s) is effective in preventing recurrence. When recurrence occurs, additional gland removal achieves resolution. Minor salivary gland removal should be incorporated as a standard component of the surgical protocol for lower lip mucocele.